ANALISIS KONTRIBUSI PENDAPATAN BADAN USAHA MILIK DAERAH TERHADAP PENDAPATAN ASLI DAERAH PEMERINTAH PROVINSI KALIMANTAN TIMUR - Abdul Rachim; Zulkifli (University of Widya Gama Mahakam Samarinda, 2022)
This study uses descriptive data in the form of time series, from the data analyzed proportionally, so that it can be seen the proportion of local revenue from 8 regional companies. Then the data provided by the Economic Bureau of the Regional Secretariat of East Kalimantan Province, there are 8 Regional Owned Enterprises, namely PT. Bankaltimtara, PT Migas Mandiri Pratama, PT, Melati Bahakti Satya, PT. East Kalimantan Electricity, PT Agro Kaltim Utama, PT Jamkrida East Kalimantan, PT. Bara Kaltim Prosperous, PT Forestry Silva Kaltim Sejahtera From the eight regional companies, data on the results of regionally owned companies and the management of regional assets are separated and then a comparison is made against the Original Regional Income of the Province of East Kalimantan. amounting to Rp. 5,145,580,600,- or its contribution to Regional Original Revenue is 5.60%, then in 2016 it was Rp. 167,385,377,650,- with Rp. 4,029,384,843,890,- or 4.15% in 2017 Rp. 208.807.497.550.- with Rp. 458,751,727,470,- or 4.55% in 2018 Rp. 199,302,498,960,- with 5,802,442,683,950,- or 3.43%, in 2019 Rp. 392,979,951,610,- with 6,358,271,910,840,- or 6.17% and in 2020 Rp. 135,154,822,000,- with 4,116,573,388,000,- or 3.28%